Acute Effects of Postactivation Potantiation on Explosive Strength Performance in Fitness Athletes - Kilincarslan, Gökmen; Ilbak, Ismail; Balyamez, Kenan; Dolanbay, Bedrettin (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this research is to examine the effects of postactivation potantiation (PAP) on explosive strength performance in terms of the rest period and also to determine the optimal resting time for generating explosive strength after the PAP protocol. Methods: Ten fitness athletes were recruited for this study. The mean age of the participants group of the research was 26.60±1.07, their height was 178.50±3.02, their weight was 80.00±4.49, their maximal squat repetition performance (1-RM) was 130±7.45, their vertical jump performance was 53.80±1.98 and their explosive strength performance was 14.50±.47. In this research, measurements were completed on five seperate days with 72 hours intervals. On the first measurement day, the athletes’ height and weight measurements, 1-RM squat measurements, vertical jump performance measurements were taken and explosive strength levels were calculated using the Lewis formula. On the second measurement day, 5 repetitions were performed with 85% of the 1-RM squat and after 15 seconds of rest, the vertical jump performance test was measured. On the third measurement day, 5 repetitions of 1-RM squats with 85% were performed and after 3 minutes of rest, the vertical jump performance test was measured. On the fourth measurement day, 5 repetitions of 1-RM squat with 85% were performed and after a rest period of 6 minutes, the vertical jump performance test was measured. Finally, on the fifth measurement day, 5 repetitions of 1-RM squats with 85% were performed and after 9 minutes of rest, the vertical jump performance test was measured. After all measurements, explosive strength levels were calculated using Lewis formula. Passive rest was performed between the exercise and the measurement. Results: It was determined that explosive strength performance was negatively affected 15 seconds after the loading applied within the scope of the PAP protocol, and the difference between the pre-test and the post-test was statistically significant. Bat it was determined that there was no statistical difference between the pre-test and post-test in explosive strength performance 3 minutes after the loads applied within the scope of the PAP protocol. But also it was observed that the explosive strength performance was positively affected 6 minutes after the loading applied within the scope of the PAP protocol, and the difference between the pre-test and the post-test was statistically significant. Finally, it was determined that there was no statistical difference between the pre-test and post-test in explosive strength performance 9 minutes after the loading applied within the scope of the PAP protocol. Conclusion: As a result of this research, it has been determined that the optimal resting time for explosive strength generation is 6 minutes after the loading applied within the scope of the PAP protocol. In addition, it was determined that explosive strength performance was negatively affected after a short rest period of 15 seconds after the loading applied within the scope of the PAP protocol. In this context, it can be said that optimum performance can occur when fatigue is greatly reduced but the PAP effect is still present.